Laser refrigeration of gas filled hollow-core fibres - Sommer, C.; Joly, Nicolas; Ritsch, H.; Genes, Claudiu (AIP Advances, 2019)
We evaluate prospects, performance and temperature limits of a new approach to macroscopic scale laser refrigeration. The considered refrigeration device is based on exciplex-mediated frequency up-conversion inside hollow-core fibers pressurized with a dopant - buffer gas mixture. Exciplexes are excited molecular states formed by two atoms (dopant and buffer) which do not form a molecule in the ground state but exhibit bound states for electronically excited states. The cooling cycle consists of absorption of laser photons during atomic collisions inducing light assisted exciplex formation followed by blue-shifted spontaneous emission on the atomic line of the bare dopant atoms after molecular separation. This process, closely related to reversing the gain mechanism in excimer lasers, allows for a large fraction of collision energy to be extracted in each cycle. The hollow-core fiber plays a crucial role as it allows for strong light-matter interactions over a long distance, which maximizes the cooling rate per unit volume and the cooling efficiency per injected photon while limiting re-absorption of spontaneously emitted photons channeled into unguided radiation modes. Using quantum optical rate equations and refined dynamical simulations we derive general conditions for efficient cooling of both the gas and subsequently of the surrounding solid state environment. Our analytical approach is applicable to any specific exciplex system considered and reveals the shape of the exciplex potential landscapes as well as the density of the dopant as crucial tuning knobs. The derived scaling laws allow for the identification of optimal exciplex characteristics that help to choose suitable gas mixtures that maximize the refrigeration efficiency for specific applications.
CRIS-Team Scopus Importer:2019-10-29